The Influence of Health Education on Sexually Transmitted Diseases inAdolescents: A Literature Review - Aswin Susanto; Annisa Nurrachmawati; Nur Rohmah (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Adolescents are vulnerable to sexually transmitted diseases (STDs) due to limited knowledge, permissive sexual attitudes, and lack of access to reproductive health information. Literature from community-based research shows that adolescents’ awareness and understanding of reproductive health remain low, increasing their risk of STDs. Health education is an important effort to improve knowledge and prevent STD transmission among adolescents. Objective : This literature review aims to determine the effect of health education on adolescents’ knowledge and attitudes toward sexually transmitted diseases through various school-based media, including leaflets, booklets, lectures, and videos. Research Methods/ Implementation Methods : The reviewed studies used pre-experimental (one group pretest-posttest) and quasi-experimental designs with control groups. Participants were high school students or adolescents, and questionnaires were distributed before and after the intervention. Data were analyzed using statistical tests such as Paired t-test or Wilcoxon signed-rank test. Results : Findings show a significant improvement in adolescents’ knowledge and attitudes after receiving health education through interactive lectures and visual media such as leaflets or booklets. The use of simple, engaging language and interactive methods proved effective in increasing understanding of STD prevention and awareness of risky sexual behaviors. Conclusion/Lesson Learned : Health education effectively enhances adolescents knowledge, attitudes, and behaviors in preventing sexually transmitted diseases. Combining visual media with interactive lectures yields better outcomes than written materials alone